Project-based learning as a way of formation of ecological competence of students - Cherednichenko, Galina; Nikitenko, Olga (My University, 2023)
One of the effective teaching methods, forms of organization of the educational process and educational technology in the formation of environmental competence both at the level of school and university education is recognized as project-based learning. Project-based learning is learning through the inclusion of students in project activities. Also through the project approach a student has the opportunity to work a group to develop social skills and especially skills in collaborating with others.

Одним із ефективних методів навчання, форм організації навчального процесу та освітніх технологій у формуванні екологічної компетентності як на рівні шкільної, так і вузівської освіти визнано проектне навчання. Проектне навчання – це навчання через включення студентів в у проектну діяльність. Крім того, завдяки проектному підходу студент має можливість працювати в групі для розвитку соціальних навичок і особливо навичок співпраці з іншими.
Keywords: кафедра ділової іноземної мови та міжнародної комунікації; project-based learning; cooperative learning; ecological competence; проектне навчання; кооперативне навчання; екологічна компетентність